Building demand-led and gender-responsive breeding programs - Polar, Vivian; Teeken, Béla; Mwende, J.; Marimo, Pricilla; Tufan, Hale Ann; Ashby, Jacqueline A.; Cole, Steven M.; Mayanja, S.; Okello, J.J.; Kulakow, Peter A.; Thiele, Graham (Springer, 2022)
Gender-responsive breeding is a new approach to making sure modern breeding takes advantage of opportunities to improve gender equality in agriculture. Conventional research on the acceptability of modern varieties has scarcely addressed gender differences during adoption studies. Gender-responsive breeding starts from a different premise that adoption and social impact will be enhanced if gender is addressed at early stages of variety design and priority setting in breeding. However, until recently, there was no concrete way to integrate gender considerations into the practice of breeding. This chapter draws lessons for the future from three RTB breeding programs innovating with gender-responsive breeding with a focus on piloting novel tools. The new G+ tools are designed to help gender researchers and breeders make joint, evidence-based decisions about the significance of gender differences for customer targeting and trait prioritization in variety development. Their piloting in the context of each program’s practice of gender-responsive breeding throws light on some valuable good practices that contributed to successful innovation.